2023
DOI: 10.1021/acs.inorgchem.3c01475
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Benzylation of White Phosphorus

Abstract: Organophosphorus compounds (OPCs) have wide application in organic synthesis, material sciences, and drug discovery. Generally, the vast majority of phosphorus atoms in OPCs are derived from white phosphorus (P 4 ). However, the large-scale preparation of OPCs mainly proceeds through the multistep and environmentally toxic chlorine route from P 4 . Herein, we report the direct benzylation of P 4 promoted by visible light. The cheap and readily available benzyl bromide was used as a benzylation reagent, and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Then a series of experiments were conducted to further explore the mechanism. Without blue light, photocatalyst or NaOAc, the yields diminished obviously, which confirmed that blue light, photocatalyst and NaOAc were important in the reaction system (Table 1, entries [15][16][17]. Adding additional reductants also didn't enhance the yield (Table S4 in the Supporting Information), which was consistent with our mechanism that Br À and NaOAc could act as proper reductants in our system.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Then a series of experiments were conducted to further explore the mechanism. Without blue light, photocatalyst or NaOAc, the yields diminished obviously, which confirmed that blue light, photocatalyst and NaOAc were important in the reaction system (Table 1, entries [15][16][17]. Adding additional reductants also didn't enhance the yield (Table S4 in the Supporting Information), which was consistent with our mechanism that Br À and NaOAc could act as proper reductants in our system.…”
Section: Resultssupporting
confidence: 85%
“…Further screening the concentration of P 4 indicated that 2 mL THF (0.0125 M P 4 ) was optimal (Table 1, entries 12-14). In addition, the lack of blue light, fac-Ir(ppy) 3 or NaOAc led to an obvious decrease in the yield (Table 1, entries [15][16][17]. Therefore, the reaction condition in entry 12 was chosen as the optimal one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations